2018
DOI: 10.5194/angeo-36-899-2018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal characteristics of small- and medium-scale gravity waves in the mesosphere and lower thermosphere over the Brazilian equatorial region

Abstract: Abstract. The present work reports seasonal characteristics of small- and medium-scale gravity waves in the mesosphere and lower thermosphere (MLT) region. All-sky images of the hydroxyl (NIR-OH) airglow emission layer over São João do Cariri (7.4∘ S, 36.5∘ W; hereafter Cariri) were obtained from September 2000 to December 2010, during a total of 1496 nights. For investigation of the characteristics of small-scale gravity waves (SSGWs) and medium-scale gravity waves (MSGWs), we employed the Fourier two-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Balan et al (2012) mentioned that, under these conditions, and considering the absence of severe magnetic disturbances, the tides and waves originating in the lower atmosphere can be expected to register their effects in the thermosphere and ionosphere more easily. Using all-sky imaging, Essien et al (2018) showed that the occurrence of smallscale (SSGWs) and medium-scale (MSGWs) gravity waves over São João do Cariri from 2000 to 2010 was higher in 2009 followed by 2008. During 2009, 289 events of SSGW and 66 events of MSGW were identified on 199 nights of observations (175 with a clear sky and 24 with clouds).…”
Section: Simultaneous Ils and Those That Are Connected To The F Regionmentioning
confidence: 99%
“…Balan et al (2012) mentioned that, under these conditions, and considering the absence of severe magnetic disturbances, the tides and waves originating in the lower atmosphere can be expected to register their effects in the thermosphere and ionosphere more easily. Using all-sky imaging, Essien et al (2018) showed that the occurrence of smallscale (SSGWs) and medium-scale (MSGWs) gravity waves over São João do Cariri from 2000 to 2010 was higher in 2009 followed by 2008. During 2009, 289 events of SSGW and 66 events of MSGW were identified on 199 nights of observations (175 with a clear sky and 24 with clouds).…”
Section: Simultaneous Ils and Those That Are Connected To The F Regionmentioning
confidence: 99%
“…This quantity can be used to classify gravity waves. Small-scale gravity waves are defined as having a horizontal wavelength λ h < 100 km and a period T < 45 min [12,13]. On the other hand, medium-scale gravity waves go from a hundred kilometers and their period can be of several hours [12,13].…”
Section: U(x Y)mentioning
confidence: 99%
“…Small-scale gravity waves are defined as having a horizontal wavelength λ h < 100 km and a period T < 45 min [12,13]. On the other hand, medium-scale gravity waves go from a hundred kilometers and their period can be of several hours [12,13]. Since equation (5) does not contain information about the period, we will only distinguish between these two types of gravity waves by analyzing their horizontal wavelength.…”
Section: U(x Y)mentioning
confidence: 99%
“…To estimate horizontal AGW parameters (e.g., observed period, wavelength, and direction of propagation) in the OH images, two techniques were used: (1) the two‐dimensional fast Fourier transform and cross‐correlation spectrum (Garcia et al, 1997) and (2) analysis of keograms (e.g., Shiokawa et al, 2009). The first technique is often used to estimate parameters of small‐scale gravity waves, and the second one is better used to study medium‐scale gravity waves (e.g., Campos et al, 2016; Essien et al, 2018; Paulino et al, 2011).…”
Section: Image Analysis and Resultsmentioning
confidence: 99%